Post-remagnetisation vertical axis rotation and tilting of the Murihiku Terrane (North Island, New Zealand). Issue 1 (2nd January 2018) - van de Lagemaat, Suzanna H. A.; Boschman, Lydian M.; Kamp, Peter J. J.; Langereis, Cor G.; van Hinsbergen, Douwe J. J.
ABSTRACT: We collected palaeomagnetic sample sets from Murihiku Terrane, North Island to constrain its palaeolatitude during the Late Triassic–Jurassic. The majority of the sample host rocks were remagnetised. However, a few samples show a magnetic signal that possibly recorded a primary remanent magnetisation. These samples preliminarily indicate that Murihiku Terrane was located at c. 63°S during the Early Jurassic. The remagnetised samples reveal significant post-remagnetisation tectonic rotation and tilting of the host rocks. We estimated an 83 ± 5 Ma timing of remagnetisation by plotting the palaeolatitude data on the apparent polar wander path of northern Zealandia. Samples from southernmost sites have lower inclination, which we interpret as reflecting eastward post-remagnetisation tilt of this region by 20°. In addition, declination data indicate large-scale post-remagnetisation rotation of Port Waikato and Awakino Gorge areas. This study contributes to the ongoing debate on the age and tectonic origin of oroclines in New Zealand basement.